2019
DOI: 10.1007/s00294-018-00928-w
|View full text |Cite
|
Sign up to set email alerts
|

Quiescence, an individual journey

Abstract: Quiescence is operationally characterized as a temporary and reversible proliferation arrest. There are many preconceived ideas about quiescence, quiescent cells being generally viewed as insignificant sleeping G1 cells. In fact, quiescence is central for organism physiology and its dysregulation involved in many pathologies. The quiescent state encompasses very diverse cellular situations depending on the cell type and its environment. This diversity challenges not only quiescence uniformity but also the univ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 65 publications
3
17
0
Order By: Relevance
“…How frequently do cells experience this naturally-underlicensed cell cycle in vivo? Cell cycle re-entry from quiescence is common in tissues that naturally turn over cell populations (Sosa et al, 2014;Sagot and Laporte, 2019;Wells et al, 2013). One might imagine however, that one risky cell cycle is a small contributor to overall genome instability.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…How frequently do cells experience this naturally-underlicensed cell cycle in vivo? Cell cycle re-entry from quiescence is common in tissues that naturally turn over cell populations (Sosa et al, 2014;Sagot and Laporte, 2019;Wells et al, 2013). One might imagine however, that one risky cell cycle is a small contributor to overall genome instability.…”
Section: Discussionmentioning
confidence: 99%
“…Cell cycle quiescence, or "G0," is a reversible cell cycle exit to a nondividing state. G0 is distinct from a G1 arrest; it is an active state requiring upregulation of anti-apoptotic, anti-senescent, and anti-differentiation genes as well as repression of cell cycle genes (Coller et al, 2006;Sang et al, 2008;Litovchick et al, 2007;Sagot and Laporte, 2019). The longer G1 phase during re-entry likely reflects the need to reactivate and express genes repressed in G0 and other fundamental differences in G1 regulation.…”
Section: Introductionmentioning
confidence: 99%
“…Quiescence is defined as a reversible cellular state from which the cells are able to re-enter the proliferative cycle in response to certain promitogenic factors, including cellextrinsic environmental signals (e.g. injury or tumor acidification) and cell-intrinsic regulatory mechanisms [1,2]. Scientific literature to date supports the existence of quiescent cancer cells in many tumor types, including breast, liver and pancreatic cancer, acute myeloid leukaemia, melanoma, and glioblastoma [3,4].…”
Section: Quiescent Tumor Cells Represent a Clinical Problemmentioning
confidence: 99%
“…In the wild, unicellular organisms are most frequently quiescent, waiting for signals to re-proliferate, which are as diverse as the presence of specific nutrients, temperature or the level of oxygen (Gray et al, 2004;Lewis & Gattie, 1991). Two decades of research have revealed that quiescent cells are much more complicated that insignificant sleeping G1 cells and are of major importance for many biology processes (Sagot & Laporte, 2019a, 2019b. Saccharomyces cerevisiae is proved to be an important model for the eukaryotic quiescent state (Gray et al, 2004;Guidi et al, 2015;Klosinska, Crutchfield, Bradley, Rabinowitz, & Broach, 2011;Rutledge, Russo, Belton, Dekker, & Broach, 2015;Sagot & Laporte, 2019b).…”
Section: The Cell Biology Of Quiescent and Non-quiescent Yeast Cell Imentioning
confidence: 99%
“…Two decades of research have revealed that quiescent cells are much more complicated that insignificant sleeping G1 cells and are of major importance for many biology processes (Sagot & Laporte, 2019a, 2019b. Saccharomyces cerevisiae is proved to be an important model for the eukaryotic quiescent state (Gray et al, 2004;Guidi et al, 2015;Klosinska, Crutchfield, Bradley, Rabinowitz, & Broach, 2011;Rutledge, Russo, Belton, Dekker, & Broach, 2015;Sagot & Laporte, 2019b). Still, the quiescent cell definition and mechanisms of transition to the Q state and its evolutionary consequences are the subject of a constant debate and fascinating discoveries (Krishna & Laxman, 2018;Sagot & Laporte, 2019a, 2019bWloch-Salamon, Fisher, & Regenberg, 2017).…”
Section: The Cell Biology Of Quiescent and Non-quiescent Yeast Cell Imentioning
confidence: 99%